THE INFLUENCE OF MUDHARABAH AND MUSYARAKAH FINANCING ON THE FINANCIAL PERFORMANCE OF SHARIA BANKING IN INDONESIA - -, Nur Arnis Irmawati; Frihatni, Andi Ayu; Budiono, I Nyoman (Islamic Financial And Accounting Review, 2024)
Mudharabah financing refers to income derived from a partnership arrangement in which the first party provides the full capital, while the second party is responsible for managing the funds. Profits from the business venture are distributed according to a mutually agreed contract, whereas any losses are entirely borne by the Islamic bank, unless the fund manager is proven to have acted intentionally, negligently, or in breach of the agreement. In contrast, musyarakah financing is income obtained from a cooperative agreement between a capital provider and a fund manager for a specific business, in which both parties agree to share profits and bear the risks based on a predetermined mutual agreement. This study aims to investigate whether musyarakah and mudharabah financing influence the financial performance of Islamic banking in Indonesia. The research applies an associative quantitative method, utilizing secondary data collected through documentation techniques. Data were analyzed using SPSS version 25, with classical assumption tests and hypothesis testing employed to assess the relationships. The research findings indicate that mudharabah financing, when examined individually, does not have a significant impact on financial performance. This is supported by the t-test results, where the calculated t-value (1.791) is less than the t-table value (2.06), and the significance value (0.087) exceeds 0.05. Similarly, musyarakah financing also does not have a significant influence on financial performance, as shown by the t-test result where the calculated t-value (0.274) is less than the t-table value (2.06), with a significance value of 0.786, which is greater than 0.05. However, when tested simultaneously, mudharabah and musyarakah financing together show a significant influence on financial performance. This is demonstrated by the F-test result, in which the calculated F-value (4.244) is greater than the F-table value (3.36), and the significance level (0.027) is below the 0.05 threshold.